(untitled) (Psychology Travelogs, 2024)
The article presents the results of the analysis of the impact of the program of psychological support for the professional health of managers of trade enterprises during the war. The set of methods for diagnosing the level of occupational health of the examinees and indications for the use of the author’s program of psychological support of the occupational health of the representatives of the experimental group were determined, and its effectiveness was clarified. Thus, positive changes in the indicators of methods that diagnose the level of professional health of managers of trade enterprises of the experimental group were proven. This is confirmed by a significant improvement in the general index of the health scale and its variables, which compared to the control group in the experimental group achieved: a) a high level of spiritual health and an average level of psychological and physical, as well as physical activity and exercise, the use of preventive health practices, which determined the average level of the general index of the lifestyle scale; b) the resource efficiency index improved to an average level due to a significant increase in the amount of assets and a decrease in the amount of losses; c) indicators of professional burnout on the scale of emotional exhaustion and depersonalization, which reached average values, significantly decreased; d) both the general level of professional vitality and its components – professional involvement and professional control – rose to average levels, as well as the emotional component significantly decreased and the motivational and professional components increased to average values; e) the impact on the professional health of managers: psychological, physical and resource factors significantly decreased, which led to the improvement of the professional health of managers of commercial enterprises of the experimental group from a low level to an average level.